ZnF2/ZnS heterostructures@NC doped porous carbon nanofibers as interlayers for stable lithium metal anodes. (1st February 2022) - Wei, Liying; Deng, Nanping; Zhao, Huijuan; Ju, Jingge; Wang, Gang; Wang, Xiaoxiao; Kang, Junbao; Kang, Weimin; Cheng, Bowen
Abstract: Lithium (Li) metal is deemed as a promising anode for next-generation high-energy-density battery. However, the rebellious dendrites growth leads to the low Coulombic efficiency and safety hazards, which has been a key challenge in the application of Li metal anode. Herein, the ZnF2 /ZnS heterostructures and N-doped carbon decorated porous carbon nanofibers (ZnF2 /ZnS/NC/PCNFs) are fabricated through the electro-blow spinning (EBS), metal-organic framework (MOF)-assisted method, and carbonization process. And its application performances as coating functional interlayer of lithium metal batteries (LMBs) to suppress the Li dendrites growth are systematically researched. The conductive interconnected skeleton of NC/PCNFs provides convenient electrons/ions transmission channels and reduces local current density. The lithiophilic ZnF2 and ZnS nanoparticles can trigger similar alloying reaction with Li-ions to guide the uniform Li deposition. In particular, the inbuilt electric field triggered at the interface of ZnF2 /ZnS heterostructures improves charge transfer and surface reaction kinetics. Combining with these merits, the Li|LiFePO4 (Li|LFP) cells with ZnF2 /ZnS/NC/PCNFs deliver an optimal initial discharge capacity of 143.2 mAh g −1 and capacity retention rate of 93.6% after 600 cycles at 1 C. Moreover, the Li|Li symmetric cells show lower overpotential than that without the interlayer. Extraordinarily, the lithium-sulfur (Li|S) cells with ZnF2 /ZnS/NC/PCNFs also display excellent cycle stability due to the strong captured or adsorbed ability to dissolved lithium polysulfides. All these results reveal that the utilization of the ZnF2 /ZnS/NC/PCNFs interlayer provides new insight for protecting the Li metal anode and improving the electrochemical properties and safety of LMBs. Graphical abstract: Image 1 Highlights: The ZnF2 /ZnS/NC/PCNFs interlayer was successfully prepared. The interlayer provided convenient ions/electrons transmission channel. ZnF2 /ZnS heterostructures could enhance the charge transfer kinetics. The interlayer could inhibit the Li dendrites growth for LMBs and absorb lithium polysulfides for Li.|S batteries.